Literature Review: Analysis of the Application of Fiscal Reconciliation in Some Companies - Sutardi, Fitrah Diraya; Sidik, Nur Halimah; Situngkir, Tiar Lina (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Fiscal reconciliation is the process of adjusting commercial financial statements with tax calculations carried out to meet applicable tax regulations and to solve the differences between fiscal financial reports and commercial financial reports. This process ensures that the company complies with tax regulations and stays clear of possible penalties or fines. Due to differences in tax and accounting procedures that may have an impact on financial statements and tax liabilities, analysis of the application and computation of fiscal reconciliation in many businesses is a pertinent topic. Together with commercial financial reports, fiscal financial reports are created, thus even though commercial or business financial reports are prepared based on business accounting principles, taxation provisions are dominant in the reporting process of financial statements for companies’ tax payments. Previous research has shown significant discrepancies between the results of commercial financial statements and fiscal calculations, often due to differences in revenue and cost recognition between commercial and fiscal accounting. The method determined through this research is a comparative literature review. The result of this research shows that some companies' corrections are not in line with tax regulations, which has an impact on how much income tax has already been paid and reported by these companies. Since deferred tax has been shown to significantly and favorably affect corporate income tax, the management of the company should pay taxes right away to lower the overall tax burden. The findings of this study suggest that corporate entities should do fiscal reconciliation due to discrepancies in cost recognition between Indonesian accounting standards and fiscal legislation. Keywords: Fiscal Analysis, Fiscal Reconciliation, Manufacturing Companies